2021
DOI: 10.1186/s12888-021-03146-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of SES on the association between childhood parental death and adulthood suicidal ideation: a mediation analysis using longitudinal dataset in South Korea

Abstract: Background We sought to examine the association between childhood experience of parental death (CEPD) and adulthood suicidal ideation, and the mediating role of adulthood SES in the association. Methods We analyzed a nationally representative dataset of 8609 adults from the Korea Welfare Panel Study, which is a longitudinal cohort dataset in South Korea. CEPD was measured using a question: “During your childhood (0-17 years old), have you experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Another type of mental health problem related to childhood adversities was suicidal ideation and suicidal attempt. 30 40 Children with a parental history of suicide had more risk of suicide as well; this idea was caused by disruption of self-regulation. In addition, they were more likely to be depressed and tended to conduct self-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Another type of mental health problem related to childhood adversities was suicidal ideation and suicidal attempt. 30 40 Children with a parental history of suicide had more risk of suicide as well; this idea was caused by disruption of self-regulation. In addition, they were more likely to be depressed and tended to conduct self-injury.…”
Section: Discussionmentioning
confidence: 99%
“…The declined physical condition and the reduced independence and social contact may intensify older adults' negative perceptions of life and living in nursing homes, resulting in poor social support, strong loneliness and high risk of suicidal ideation. Recently, studies were identified investigating the working paths of risk factors contributing to suicidal ideation among the youth (Sarkisian et al., 2021 ; Yoon et al., 2021 ). However, little evidence has been generated about whether such working paths may influence the suicidal ideation among older adults in nursing homes.…”
Section: Introductionmentioning
confidence: 99%